The diagnostic value of next-generation sequencing technology in sepsis - Cao, Xiao-guang; Zhou, Shu-sheng; Wang, Chun-yan; Jin, Kui; Meng, Hua-dong (Frontiers in Cellular and Infection Microbiology, 2022)
Abstract Objective: This study aims to assess the clinical utility of next‐generation sequencing in the diagnosis of sepsis. Method: A prospective study was conducted on patients with a high suspicion of sepsis and a lack of pathogen results from January 2017 to December 2021. Blood samples were taken from the patients to perform NGS, blood culture, WBC, PCT, CREA, ALB, and CRP tests. Meanwhile, the data from the two groups were compared and analyzed. Results: The clinical diagnosis was considered the "gold standard". Among the 83 patients, 53 patients met the clinical diagnostic criteria for sepsis, while 30 were non-sepsis. Positive rates for blood culture were 10.84% (9 patients) and 78.31% (64 patients) for NGS, PCT, CREA, and CRP levels were higher in the sepsis group than in the non-sepsis group, while ALB levels were lower (P<0.05). ALB and NGS were linked to sepsis using logistic regression. The area under the receiver operating characteristic (ROC) curve, sensitivity and specificity were 0.728, 58.06%, 80.95% and 0.857, 95.16% and 76.19%, respectively. The combination's sensitivity and specificity were 93.55% and 85.71%. The area under ROC curve was 0.935, greater than that of albumin and NGS (P<0.05). Conclusion: The positive rate of pathogens detected by NGS was high; NGS and ALB levels can be used early screening. Their combination is more powerful.